High Throughput Implementation of RIPEMD-160 using Unfolding Transformation - Shamsiah binti, Suhaili; Watanabe, Takahiro; Maimun, Binti Huja Husin; Kuryati, Binti Kipli; Norhuzaimin, Bin Julai; Rohana, Binti Sapawi (2018)
Cryptographic hash function is important for digital signature, Hash Message Authentication Code (HMAC) and other data security application. There are different types of hash function such as MD5, SHA-1, RIPEMD-160, SHA-2 and others. In this paper, RIPEMD-160 algorithm has been chosen as one of the hash functions because of the parallel inner structure of this algorithm. The objective of this research is to design and implement RIPEMD-160 with high throughput using different types of methodology. Three types of methodology are iterative, pipelining and unfolding design. These methodologies were applied to this RIPEMD-160 design in order to analyze the results of maximum frequency, area implementation and throughput of the design on Arria II GX FPGA family device. By using unfolding transformation, the throughput of the RIPEMD-160 can be improved which is about 1029.50 Mbps.